Dissolution of cork biopolymers in biocompatible ionic liquids - Garcia, Helga; Ferreira, Rui; Petkovic, Marija; Ferguson, Jamie L.; Leitão, Maria C.; Gunaratne, H. Q. Nimal; Seddon, Kenneth R.; Rebelo, Luís Paulo N. Luis Paulo N.; Silva Pereira, Cristina; Leitão, Maria C. (Green Chemistry, 2010)
Classically, the best attempts to separate suberin from cork biopolymers have resulted in low efficiency; here, we report a class of biocompatible and biodegradable cholinium-based ionic liquids, the cholinium alkanoates, which show a highly efficient and specific dissolution of the suberin domains from cork biopolymers.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Cork; cork biopolymers dissolution; ionic liquids; suberin (voyant)